The Development E-Book Balancing Ecosystem Based on Education Character for Students’ Elementary School - Candra Dewi (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
Elementary school students need to preserve nature by maintaining the balance of the ecosystem. Nature conservation efforts in protecting the ecosystem is one form of character education and knowing the feasibility of these media. This article was to develop a character education-based ecosystem balance e-book. This study used the research and development method of Borg and Gall theory which was only carried out with ten development stages consisting of research and information gathering; planning; develop preliminary form product; preliminary field test; main product revision; main field testing; operational product revision; operational field testing final product revision; dissemination and implementation. Data analysis used during development was descriptive analysis, percentage techniques, and classical completeness. In the validation stage the expert showed the average percentage value of material experts was 87%, media experts were 88.2%, linguists were 89.4% very feasible criteria. And the average practicality value is 3.55. Based on this, the products produced in this study are said to be suitable for use in learning. Keywords: Development E-Book, Ecosystem Balance, Education Character